PELAKSANAAN KEGIATAN PERILAKU HIDUP BERSIH DAN SEHAT DI ERA COVID-19 DI DESA CERUKCUK KECAMATAN TANARA - Muhammad Rinaldi Pratama; Deris Desmawan; Selly Apriyani; Febri Hikmah Frihatini; Ikbal; Fikri Khusaini; Ira Savira; Sarnimah; Agung Permana; Muhamad Syahril Anwarudin; Sintiya Elfariani; Nurazizah; Rahmah Nur Hidayah; Syefi Ersya Agustin; Afinka Ramandani Nurhidayat; Tharisa Ayu Pranovcy; Rifda Rachmanda; Juliansyah; Arief Eka Nugraha; Silvia Indah Sari; Rian Sopian; Abdul Majid Refindo; Aflah Fadilah HD (CV. Era Digital Nusantara, 2023)
Clean and Healthy Living Behavior (PHBS) is a step that needs to be done in order to create good health in the community and in the school environment. The purpose of this PHBS activity is to increase public awareness to better understand their living conditions to maintain health. With this outreach, people are able to apply a clean lifestyle in their daily life. As an educated student, by applying the third point of the tri dharma of higher education, namely self-service to the community, it must be able to reflect a clean and healthy lifestyle so that people are more aware and sensitive to it.Community service activities are carried out on Saturday and Monday, January 22-24 2022 at SDN Cerukcuk and SDN Cikeli by conducting socialization about clean and healthy living behavior (PHBS) and practicing proper hand washing and toothbrushing procedures for elementary school children into a program which can improve public health.